Fast pyrolysis char – Assessment of alternative uses within the bioliq® concept. (January 2016) - Funke, A.; Niebel, A.; Richter, D.; Abbas, M.M.; Müller, A.-K.; Radloff, S.; Paneru, M.; Maier, J.; Dahmen, N.; Sauer, J.
Highlights: Biomass residues with high ash content have been successfully pyrolysed. Separate solid/liquid product recovery after fast pyrolysis increases oil yield. Char has limited value as energy carrier due to high ash content. Near complete demineralization and activation of char was conducted. Activated carbon has potential to increase the economic feasibility of fast pyrolysis. Abstract: Experiments with a process development unit for fast pyrolysis of biomass residues of 10 kg h −1 have been performed to quantify the impact of two different product recovery options. Wheat straw, miscanthus and scrap wood have been used as feedstock. A separate recovery of char increases the organic oil yield as compared to a combined recovery of char and organic condensate (OC). Furthermore, it allows for an alternative use of the byproduct char which represents an important product fraction for the high ash biomass residues under consideration. The char produced shows little advantage over its biomass precursor when considered as energy carrier due to its high ash content. Significant value can be added by demineralizing and activating the char. The potential to increase the economic feasibility of fast pyrolysis is shown by an assessment of the bioliq® process chain.